Development of Smart Physics Card as Physics Learning Media on Temperature and Heat Material. (February 2020) - Latifah, Sri; Koderi, K; Fiteriani, Ida; Khoiruddin; Diani, Rahma
Abstract: This study aims to develop media in the form of smart physics cards in temperature and heat parameters to determine the feasibility and attractiveness of smart physics cards. This research is a development research using ADDIE model. The stages are analysis, design, development, implementation, and evaluation. Researchers analyse the curriculum and analyse the used learning media. At the design stage, researchers design smart physics cards as needed. After being designed, the smart physics card media is validated by 4 validators. At the implementation stage, smart physics cards are tested by teachers and class XI students in odd semester 2018/2019. The last stage is the evaluation; the product is evaluated as a form of final evaluation of the results of the pilot test of teachers and students. The results show that the smart physics card is very feasible and very interesting because it has been through the validation and testing stages with a percentage of achievements of 90% according to material experts, 86% according to media experts and 85% according to physics teachers of SMA/MA grade XI. The results of trials on high school/MA students of class XI showed a percentage of achievements of 84.2% with very interesting criteria. From this development research, it was concluded that the smart physics card on the material's temperature and heat meets the requirements of a very decent quality and is very interesting to use as a learning medium for students of high school/MA grade XI.